Drug-induced Myelotoxicity in Patients with Crohn’s Disease - Renaldi, Kaka; Hosea, Fransiscus Nikodemus (The Indonesian Society for Digestive Endoscopy, 2024)
As a chronic granulomatous disease, Crohn’s disease (CD) poses a significant insinuation on morbidity and low quality of life. Long-term treatment is needed to control the disease activity. Observation and evaluation of disease activity are principal practices in treating CD, and sometimes clinicians tend to overlook the adverse effects of therapy that may occur and resemble disease progression.Hereby, we presented a 76-year-old female with a 10-year history of Crohn’s disease who came to our emergency room with general weakness one week before admission. She complained of hematochezia and abdominal pain in the last month. She had been taking mesalazine 2x500 mg PO and azathioprine 2x50 mg PO in the previous three years. She was diagnosed with lung cancer six months before admission and had been prescribed erlotinib 1x150 mg PO in the last six weeks. Upon admission, pancytopenia was found in the blood study. Hematochezia, along with anemia and abdominal pain, might occur due to either disease activity or the adverse effects of the medication.Thorough observation and clinical evaluation regarding disease activity and side effects are required to manage Crohn’s disease comprehensively.